2014
DOI: 10.7755/fb.112.2-3.3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of demography on spatial distribution: movement patterns of the Albemarle Sound–Roanoke River stock of Striped Bass (Morone saxatilis) in relation to their recovery

Abstract: Abstract-We analyzed tag returns from a long-term tagging program to evaluate the movement patterns of the Albemarle Sound-Roanoke River (AR) stock of Striped Bass (Morone saxatilis) during a period of stock recovery in 1991-2008. The AR stock was found to increase its movement outside the Albemarle Sound estuary (from <4% to 15-31%) as it recovered from 1991 to 2008. Analysis with multinomial logistic regression where recapture area was modeled as a function of fish size and stock abundance indicated that Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…Growth estimation.-Striped Bass exhibited high fidelity to their stocking system, which allowed us to estimate systemspecific growth and mortality. In other studies, tagged Striped Bass have been reported by fishers in coastal waters from North Carolina to Maine (Dorazio et al 1994;Welsh et al 2007;Callihan et al 2014); thus, Striped Bass fisheries (and potential tag recovery locations) occur along the entire eastern seaboard of North America. Yet, the majority (>90%) of tag returns of stocked fish was from the same river system in which fish were initially released.…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…Growth estimation.-Striped Bass exhibited high fidelity to their stocking system, which allowed us to estimate systemspecific growth and mortality. In other studies, tagged Striped Bass have been reported by fishers in coastal waters from North Carolina to Maine (Dorazio et al 1994;Welsh et al 2007;Callihan et al 2014); thus, Striped Bass fisheries (and potential tag recovery locations) occur along the entire eastern seaboard of North America. Yet, the majority (>90%) of tag returns of stocked fish was from the same river system in which fish were initially released.…”
Section: Methodsmentioning
confidence: 85%
“…The current paradigm suggests that Roanoke River Striped Bass are a resident population that generally remains in their natal estuary (Albemarle Sound) throughout their lives, making only local spawning migrations during spring to their freshwater spawning grounds on the upper Roanoke River (Hassler et al 1981). However, a recent study by Callihan et al (2014) revealed that some members of this population, mainly larger and older fish (TL > 850 mm, age > 10), are indeed migratory and engage in seasonal coastwide migrations (north in the summer, south in the fall-winter).…”
mentioning
confidence: 85%
“…Maximum age was assumed to be 30 years. Emigration and immigration were assumed to be negligible, as studies have shown that the Neuse River Striped Bass population is mainly riverine and nonmigratory (Marshall 1977;Hawkins 1980;NCDMF and NCWRC 2013;Callihan et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…; USDOI and USDOC ; NCDMF and NCWRC ; Callihan et al. ), improved water quality (Sloan et al. ; Albert ; Richards and Rago ), and increased access to spawning habitat (NCDMF and NCWRC ) have led to recoveries of some stocks; examples include those in the Chesapeake Bay and Roanoke River (Richards and Rago ; NCDMF and NCWRC ).…”
mentioning
confidence: 99%
“…In many populations, the probability that an individual striped bass is anadromous 65 increases with fish size (Callihan et al 2014). For the AS-RR stock, most juvenile and small 66 mature striped bass remain in the AS-RR throughout the year.…”
mentioning
confidence: 99%